Análise e fabricação de antenas de microfita patch retangular: compilado de artigos publicados em 2024 - CRUZ, Leonardo França da (2024)
This work presents a compilation of articles published in 2024, aiming to develop a methodology for the parametric analysis and fabrication of microstrip antennas with a rectangular patch. The first article primarily focuses on analyzing the effects of varying the width and length of the rectangular patch on the performance of a microstrip antenna. This analysis was based on a reference antenna designed to operate at 2.4 GHz, with a patch measuring 38.03 mm in width and 29.47 mm in length, mounted on an FR4 dielectric substrate with a thickness of 1.5 mm and a relative permittivity of 4.4. The results showed that varying the patch width (W) between 50 and 200% of the reference value increases the return loss but also shifts the resonance frequency from 2.51 GHz to 1.92 GHz. On the other hand, varying the patch length (L) indicated that only the antenna with double the reference length exhibits a usable bandwidth at 2.42 GHz. The second article presents two fabrication methods for microstrip antennas and compares their feasibility and effectiveness. The first antenna was fabricated using a CNC micro-milling machine, and the second, through a corrosion method with ferric chloride. After fabrication, the return loss and VSWR of the antennas were measured using the LiteVNA-64 network analyzer and compared with simulations performed in the Ansys HFSS software. The articles demonstrated the feasibility of applying digital fabrication procedures for microstrip antennas in academic laboratories, using accessible and didactic methods.